JMO App User Behavior Analysis with Theory of Planned Behavior (Case Study: Jambi City Community) - Salwa, Shakira; Rambe, Lio Nauli; Yani, Serli Putri Andri; Borroek, Maria Rosario; Istoningtyas, Marrylinteri (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
Jamsostek Mobile application is an application as an information service feature for Employment BPJS policies which can be accessed online, one of its features is a simulation of JHT and Pension Guarantee (JP) balances. The purpose of this study is to analyze user behavior in using JMO – Jamsostek Mobile application and to find out which variables have the most influence and have the highest value compared to other variables. The method used in this study is Theory of Planned Behavior (User Behavior Theory) which is an extension of Theory of Reasoned Action (TRA) aims to look at user behavior in JMO – Jamsostek Mobile application which focuses on 5 variables, in the form of 3 independent variables namely attitude toward behavior, subjective norm, perceived behavioral control) and 2 dependent variables namely behavioral intention and behavior. The population were the people of Jambi City where the number of respondents obtained from distributing questionnaires via Google Form was 384 respondents and this data analysis technique used SmartPLS. the results of hypothesis testing have a strong level of relationship that the independent variable has an influence on the dependent variable.